An Exploration of Meaningful Work: Examining Its Correlational Effect on Affective Commitment Level of Port Service Industry Employee - Firdausi, Lutfiana; Prabandini Mulyana, Olievia (Jurnal Manajemen dan Organisasi, 2024)
Meaningful work is a psychological concept that currently become a great concern among industry and organizations. This approach focuses on the search for meaning in work amidst the increasing complexity of work, especially in the port services industry, which is one of the vital sectors in the national economy. Previous studies have proven that meaningful work could strengthen employees' emotional attachment and optimizing job satisfaction. This research aims to explore the meaningfulness of work and its association with affective commitment level in the port service industry employee. It utilizes quantitative methods to quantify 45 employees through self-administered work meaningful scale and affective commitment scale then were analyzed using descriptive statistics. This research findings indicate a significant positive correlation between the meaningfulness of work and affective commitment among employees in the port services industry. Further analysis reports that majority of employees have a high and very high level of work meaningfulness which proved to be comparable to the level of affective commitment. In general, the level of meaningfulness of work for supervisory employees is the highest among other positions.